Correlation Between C-Reactive Protein and Blood Sugar Profile and Lipid Profile in Obesity After Lifestyle Modification for 3 Months - Putri, Indah Prasetya; Santi Syafril (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2022)
Background. C-reactive protein (CRP) is a phylogenetically highly conserved plasma protein that participates in the systemic response to inflammation and its plasma concentration increases during inflammatory states. The purpose of the study was to determine the correlation between CRP and blood sugar profile and lipid profile in obesity undergoing lifestyle modification for 3 months. Method. The study was conducted on hospital nurses with BMI >25 (obesity) who were selected voluntarily. Before making lifestyle modifications (diet and physical exercise) for 3 months, patients are given lighting, understanding, and training on lifestyle modifications. Patients were examined for BMI, FPG, PPG, HbA1c, LDL, HDL, and ApoB before and after 3 months of lifestyle modification. Result. Lifestyle modification for 3 months had been performed on 20 patients with a BMI of 30.9±4.15 kg /m2 (obesity). There is a significant correlation between CRP and PPG, HbA1C, LDLC, and ApoB (p < 0.005). Conclusion. There is a significant correlation between CRP and glucose profile and lipid profile on obesity undergoing lifestyle modification for 3 months.